Pengaruh Implementasi ERP Kepada Kinerja Karyawan Saat Melakukan Work From Home (WFH) - Sidanta, Oscar; Meyliana (Jurnal Sistem Cerdas, 2023)
As the COVID-19 pandemic intensified in Indonesia in 2020, companies and organizations have devised measures in order to adapt with the absence of physical workforce presence in the workplace, including implementing work-from-home (WfH) regimes, where the employee conducts work operations from their residence. Adapting into a new working environment, however, is often a considerable challenge for companies and organizations of all stripes, especially in ensuring that users can properly adjust themselves and maintain a degree of work efficiency. The work efficiency of users while using a widespread and integrated company business solution, especially enterprise resource planning (ERP) software is often measured by the overall satisfaction of each user. To measure user satisfaction while using an ERP-based enterprise resource management system for work-from-home operations, this research attempts to conduct a survey in an institution or organization that has been sending employees to work from home by collecting responses from employees. The questionnaire will have each respondent evaluate the three relevant variables (benefits, risks and barriers) while using the ERP based system to work from home, which will then be used to measure its correlation with the users’ satisfaction relative to the three factors using the one-way ANOVA correlation method. Research results have yielded a positive correlation between the variables of system effectiveness and user satisfaction, indicating that the use of ERP is generally satisfactory to its users and that ERP systems prove beneficial in assisting organizations in their WfH regime, within the restrictions of a public health issue and beyond.